2011
DOI: 10.1016/j.ejps.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of ruthenium-based intercalators

Abstract: Multidrug resistance of bacterial pathogens is a major problem and there is a clear need for the development of new types of antibiotics. Here we investigated the antimicrobial activity of ruthenium(II) based DNA-intercalating complexes. These complexes were found to have no activity in vitro against the Gram-negative bacterium Escherichia coli, but the complexes were clearly active against the Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus. In vivo activity has also been demonstrated for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 32 publications
1
88
0
Order By: Relevance
“…This has been found to be an important component of the extracellular matrix of biofilms, and for instance DNAse treatment significantly reduces the biomass of biofilms of S. aureus and other bacteria [28]. However, a number of other DNAbinding metallo-complexes that we tested have no or barely any activity on biofilms, including the aforementioned compounds 10 and 11, as well as other compounds such as major groove-binding complexes of iron [22] or ruthenium [23] (data not shown). It is well known that many coordination complexes with copper, but not those with platinum or palladium, are redox active and can mediate DNA cleavage [17].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This has been found to be an important component of the extracellular matrix of biofilms, and for instance DNAse treatment significantly reduces the biomass of biofilms of S. aureus and other bacteria [28]. However, a number of other DNAbinding metallo-complexes that we tested have no or barely any activity on biofilms, including the aforementioned compounds 10 and 11, as well as other compounds such as major groove-binding complexes of iron [22] or ruthenium [23] (data not shown). It is well known that many coordination complexes with copper, but not those with platinum or palladium, are redox active and can mediate DNA cleavage [17].…”
Section: Discussionmentioning
confidence: 95%
“…In recent years we have investigated the antimicrobial activity of compounds containing iron, ruthenium, copper and palladium [16,[21][22][23][24]. All of these compounds have been reported to bind DNA, either through groove binding or intercalation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was however not taken forward and these compounds have not been used clinically. Interestingly, the compound was also active in an infection model [21]. In the absence of compound, the soil nematode Caenorhabditis elegans was killed within a few days by MRSA, but the presence of [Ru(2,9-Me 2 phen) 2 (dppz)] 2+ rescued the nematodes from infection.…”
Section: Dna Intercalatorsmentioning
confidence: 95%
“…A minor groove binder that has been used clinically since the 1940s is the bis-amide pentamidine (21), an important drug in the treatment against a number of protozoal diseases, including those that cause pneumocystis pneumonia, leishmaniasis and African trypanosomiasis (sleeping sickness). From studies with several analogues it was suggested that the isohelical shape of the molecule is important for interaction with the minor groove [35].…”
Section: Minor Groove Bindersmentioning
confidence: 99%